2012
DOI: 10.1371/journal.pone.0034331
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory Syncytial Virus G Protein Conserved Domain Induces a Persistent and Protective Antibody Response in Rodents

Abstract: Respiratory syncytial virus (RSV) is an important cause of severe upper and lower respiratory disease in infants and in the elderly. There are 2 main RSV subtypes A and B. A recombinant vaccine was designed based on the central domain of the RSV-A attachment G protein which we had previously named G2Na (aa130–230). Here we evaluated immunogenicity, persistence of antibody (Ab) response and protective efficacy induced in rodents by: (i) G2Na fused to DT (Diphtheria toxin) fragments in cotton rats. DT fusion did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…We chose a dose of 2x10 5 PFU that was recently reported to be sufficient to assess the efficacy of RSV vaccines (Garg et al, 2014; Johnson et al, 2014; Kim et al, 2014; Murata and Catherman, 2012; Nguyen et al, 2012; Schmidt et al, 2012). We also found that the PBS or PR8 WT group of mice that were infected with 2x10 5 PFU RSV showed a high titer of approximately up to 10 4 PFU from lungs at day 5 post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We chose a dose of 2x10 5 PFU that was recently reported to be sufficient to assess the efficacy of RSV vaccines (Garg et al, 2014; Johnson et al, 2014; Kim et al, 2014; Murata and Catherman, 2012; Nguyen et al, 2012; Schmidt et al, 2012). We also found that the PBS or PR8 WT group of mice that were infected with 2x10 5 PFU RSV showed a high titer of approximately up to 10 4 PFU from lungs at day 5 post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These problems have been attributed to an Arthus reaction to the BB component (Libon 2007). Without the BB component, the G2Na peptide induced protective immunity in cotton rats and, in previously immunized mice, it was recently shown to boost antibody titer to RSV (Nguyen et al 2012), suggesting that this approach might work to boost immunity to RSV in older adults. Another group performed vaccination studies in naive mice with a similar peptide (amino acids 131–230) and mucosal immunization, without the addition of an adjuvant.…”
Section: Vaccine Implicationsmentioning
confidence: 99%
“…Based on these findings, strategies for developing a safer RSV vaccine that circumvents FI-RSV-induced VED should include the induction of both Treg cells in lung and high levels of neutralizing Abs (20,45,46). Among all of the 11 viral proteins of RSV, only G and F glycoproteins contain neutralizing epitopes and induce long-term neutralizing Abs (47)(48)(49). For this reason, both have been considered as ideal candidates for RSV vaccine development.…”
mentioning
confidence: 99%